Mechanism of Ni-Catalyzed Oxidations of Unactivated C(sp3)–H Bonds - Qiu, Yehao; Hartwig, John F (Journal of the American Chemical Society, 2020)
The Ni-catalyzed oxidation of unactivated alkanes, including the oxidation of polyethylenes, by meta-chloroperbenzoic acid (mCPBA) occur with high turnover numbers under mild conditions, but the mechanism of such transformations has been a subject of debate. Putative, high-valent nickel-oxo or nickel-oxyl intermediates have been proposed to cleave the C–H bond, but several studies on such complexes have not provided strong evidence to support such reactivity toward unactivated C(sp3)–H bonds. We report mechanistic investigations of Ni-catalyzed oxidations of unactivated C–H bonds by mCPBA. The lack of an effect of ligands, the formation of carbon-centered radicals with long lifetimes, and the decomposition of mCPBA in the presence of Ni complexes suggest that the reaction occurs through free alkyl radicals. Selectivity on model substrates and deuterium-labeling experiments imply that the m-chlorobenzoyloxy radical derived from mCPBA cleaves C–H bonds in the alkane to form an alkyl radical, which subsequently reacts with mCPBA to afford the alcohol product and regenerate the aroyloxy radical. This free-radical chain mechanism shows that Ni does not cleave the C(sp3)–H bonds as previously proposed; rather, it catalyzes the decomposition of mCPBA to form the aroyloxy radical.